anonymous
  • anonymous
Show that
Collaborative Statistics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Show that: \[|cosz|^{2}= \cos^{2}x+\sinh^{2}x\] Hint: using \[\cos z = \frac{ e^{iz} + e^{-iz}}{ 2 }\] \[\sin z = \frac{ e^{iz} - e ^{-iz} }{ 2i }\] \[\cosh z = \frac{ e^{z}+e^{-iz} }{ 2 }\] \[\sinh z = \frac{ e^{z} - e^{-z} }{ 2 }\]
anonymous
  • anonymous
Sorry I MEAN, show that \[|\cos z|^{2} = \cos^{2} x + \sinh^{2}y\]
anonymous
  • anonymous
would you kindly help me again @niksva ??

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Take LHS first (cosz)^2 replace z with x +iy cos(x+iy) = cos(x)cos(iy) - sin(x)sin(iy)
anonymous
  • anonymous
as cos(iy) = coshy and sin(iy) =i sinhy therefore cosz = cos(x)cos(hy)-i sin(x)sin(hy)
anonymous
  • anonymous
@gerryliyana after squaring and applying (a-b)^2 formula , the equation become difficult to solve
anonymous
  • anonymous
i've tried.., but didn't match,
anonymous
  • anonymous
how did u approach the problem?
anonymous
  • anonymous
using hint above..., i tried, one by one.., hbu?? it's make sense ?
anonymous
  • anonymous
how can u apply above hint in RHS?
anonymous
  • anonymous
what the next ??
anonymous
  • anonymous
my ques is as z = x + iy where x is real number and y is imaginary number can we write cosx= (e^ix+ e^-ix)/2 ???????/ according to me, we cannot write this as x is a real number
anonymous
  • anonymous
@UnkleRhaukus help?
anonymous
  • anonymous
\[\Large{ \cos z={e^{-iz}+e^{iz}\over2}\\ LHS=|\cos z|^2={1\over4}\left(e^{-2iz}+2e^{-iz+iz}+e^{2iz}\right)\\ \quad={1\over2}+{1\over4}\left[e^{-2i(x+iy)}+e^{2i(x+iy)}\right]\\ \quad=\color{red}{{1\over4}\left(2+e^{2y}+e^{-2y}\right)+{1\over4}\left(e^{-i2x}+e^{i2x}\right)}\\ RHS=\cos^2x+\sinh^2y\\ \quad={1\over4}\left(e^{-i2x}+e^{i2x}+2\right)-{1\over4}\left(e^{2y}-2+e^{-2y}\right)\\ }\] They do not seem to match!!
anonymous
  • anonymous
have idea ???
anonymous
  • anonymous
yes. you can prove it thus way: 1) get LHS = "a" 2) if you can show RHS = "a", then LHS=RHS="a" and QED. but following this, the two sides probably have an issue with the "signs"
anonymous
  • anonymous
no wait.. my bad.. I took "sin y" instead of "sinh y" \[\Large{ \cos z={e^{-iz}+e^{iz}\over2}\\ LHS=|\cos z|^2={1\over4}\left(e^{-2iz}+2e^{-iz+iz}+e^{2iz}\right)\\ \quad={1\over2}+{1\over4}\left[e^{-2i(x+iy)}+e^{2i(x+iy)}\right]\\ \quad=\color{red}{{1\over4}\left(2+e^{2y}+e^{-2y}\right)+{1\over4}\left(e^{-i2x}+e^{i2x}\right)}\\ RHS=\cos^2x+\sinh^2y\\ \quad={1\over4}\left(e^{-i2x}+e^{i2x}+2\right)+{1\over4}\left(e^{2y}-2+e^{-2y}\right)\\ \quad=\color{red}{{1\over4}\left(e^{2y}+e^{-2y}\right)+{1\over4}\left(e^{-i2x}+e^{i2x}\right)}\\ {\rm SO,}\\ \color{green}{\boxed{|\cos z|^2={1\over2}+\cos^2x+\sinh^2y}} }\]
anonymous
  • anonymous
but it's not the answer
anonymous
  • anonymous
as you see, the LHS and the RHS differ by \(1\over2\).
anonymous
  • anonymous
yes., i see, did you know why ???

Looking for something else?

Not the answer you are looking for? Search for more explanations.